2017
DOI: 10.1161/jaha.116.004995
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Incidence of Hospitalization With Lower‐Extremity Peripheral Artery Disease: Atherosclerosis Risk in Communities Study

Abstract: BackgroundCompared to coronary heart disease, heart failure, and stroke, the relationship between low socioeconomic status (SES) and peripheral artery disease (PAD) is less well established. We examined the association between SES and incidence of hospitalization with PAD and explored whether this association can be explained by traditional cardiovascular risk factors and healthcare access.Methods and ResultsA total of 12 517 participants in the Atherosclerosis Risk in Communities (ARIC) Study (1987‐1989) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 52 publications
7
51
1
1
Order By: Relevance
“…The suggestion that disparities in care for patients with PAD are due to differences in how that care is provided is contrary to the trends seen in our study, where we see patients, regardless of dual-eligibility status, receiving homogenous preoperative and postoperative care. Additionally, patient-related factors such as race have been attributed to increased risk of PAD and poor outcomes 13 25. We also performed subgroup analyses including by patient age (65 years and older vs under age 65 years), race and by hospital where surgery occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggestion that disparities in care for patients with PAD are due to differences in how that care is provided is contrary to the trends seen in our study, where we see patients, regardless of dual-eligibility status, receiving homogenous preoperative and postoperative care. Additionally, patient-related factors such as race have been attributed to increased risk of PAD and poor outcomes 13 25. We also performed subgroup analyses including by patient age (65 years and older vs under age 65 years), race and by hospital where surgery occurred.…”
Section: Discussionmentioning
confidence: 99%
“…was populated using PubMed searches, including the keywords ‘peripheral artery disease’, ‘cardiovascular disease’, ‘social determinants’, ‘socioeconomic status’, ‘mental health’ and ‘Medicare–Medicaid dual-eligible’. While table 3 is not exhaustive, it highlights the complex interactions between race,13 functional status,27 gender28 and income25 in affecting patient outcomes in PAD. Our study provides context to this prior work by adding more detail to the effect different types of insurance status can have on patient outcomes, even among those with significant comorbid illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalent atrial fibrillation at visit 4 was also identified from electrocardiograms conducted at visits 1–4 ( n = 47). Peripheral artery disease events were identified from hospitalizations on the basis of ICD-9 diagnosis codes for peripheral artery disease (440.2, 440.3, 440.4) or ICD-9 procedure codes for leg revascularization (38.18, 39.25, 39.29, 39.50) (21). Ascertainment for all events occurred through 31 December 2013.…”
Section: Methodsmentioning
confidence: 99%
“…This included any validated definite or probable hospitalization for myocardial infarction, death due to coronary heart disease, silent myocardial infarction detected at visit 3 or 4, a validated stroke event, or hospitalization or death due to heart failure (heart failure events after 2004 were adjudicated by an end point committee) (8–13). Incident peripheral artery disease was defined as the first hospitalization related to peripheral artery disease (14). Deaths were identified from state records and linkage to the National Death Index.…”
Section: Methodsmentioning
confidence: 99%